2016
DOI: 10.1589/jpts.28.2871
|View full text |Cite
|
Sign up to set email alerts
|

Effect of exercise therapy on cytokine secretion in the saliva of bedridden patients

Abstract: [Purpose] The number of bedridden patients requiring nursing care in Japan has increased sharply in recent years because of its aging population and advances in medical care and has become a major social issue. Because bedridden patients are susceptible to nursing and healthcare-associated pneumonia, it is very important to improve their immunocompetence. Therefore, the effect of exercise therapy on stimulation of cytokine secretion in the saliva of bedridden patients was investigated. [Subjects and Methods] T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Whether the key to protection is species specific or lies in the diversity or evenness of the microbial community is not fully understood, although evidence is accumulating that both diversity (45,241,263,304) as well as evenness ( 63) seem to contribute to mucosal homeostasis. However, here as well, a state of dysbiosis is not directly associated with the actual occurrence of infection: a trigger, such as increased aspiration, viral infection, poor oral hygiene, or a supine position (as seen in institutionalized or hospitalized patients) is again needed to tip the balance towards an actual acute infection (FIGURE 2) (178,209,232,233,290). For example, studies have shown that influenza A virus infection, through type I and III interferon signaling, inhibits Th17 activation and consequently suppresses IL-23 production and antimicrobial peptide production.…”
Section: A Acute Respiratory Infectionsmentioning
confidence: 99%
“…Whether the key to protection is species specific or lies in the diversity or evenness of the microbial community is not fully understood, although evidence is accumulating that both diversity (45,241,263,304) as well as evenness ( 63) seem to contribute to mucosal homeostasis. However, here as well, a state of dysbiosis is not directly associated with the actual occurrence of infection: a trigger, such as increased aspiration, viral infection, poor oral hygiene, or a supine position (as seen in institutionalized or hospitalized patients) is again needed to tip the balance towards an actual acute infection (FIGURE 2) (178,209,232,233,290). For example, studies have shown that influenza A virus infection, through type I and III interferon signaling, inhibits Th17 activation and consequently suppresses IL-23 production and antimicrobial peptide production.…”
Section: A Acute Respiratory Infectionsmentioning
confidence: 99%
“…Compared with patients in mixed wards/intensive care unit (ICU) settings, ICU patients have a higher proportion of bacterial infections ( Lansbury et al, 2020 ). These studies suggested that keen vigilance should be maintained against infections derived from the oral microbiome during infection by respiratory viruses and have uncovered risk factors such as increased inhalation, poor oral hygiene, and viral infection are related to the occurrence of respiratory infection ( Pace and McCullough, 2010 ; Krone et al, 2014 ; Iki et al, 2016 ). The mechanisms by which the oral microbiome can influence respiratory disease is complicated and multifactorial, simultaneously affected by environmental, host, and microbial factors ( Xu et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers [ 52 – 55 ] have attested that Taiji, Yijinjing Qigong, Shaolin Neigong, Wuqinxi Qigong, Liuzijue Qigong, and Baduanjin Qigong can improve the clinical symptoms, along with physical and mental health of patients with lung diseases. TCMRE projects are highly operational and cost-effective due to overburdened healthcare system [ 56 , 57 ]. Studies found that exercise may be beneficial for improving pulmonary symptoms and suppressing inflammation in discharged patients [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…KQG will promote recovery for the majority of patients and improves the living quality of patients [ 17 , 25 ]. The human immune system is able to counteract the damage of foreign microorganisms through dynamic regulation of innate immunity by TCMRE [ 40 , 57 ], and increasing muscle strength and respiratory muscle endurance to relieve dyspnea, anxieties, and tension associated with negative situations [ 25 ]. TCMRE is capable of coordinating Qi and blood, adjusting the balance of Yin and Yang from the macro theory of TCM.…”
Section: Discussionmentioning
confidence: 99%